LEGAL PROTECTION OF WOMEN VICTIMS OF DOMESTIC VIOLENCE IN TERMS OF HUMAN RIGHTS (NORMATIVE STUDY OF THE SURAKARTA CASE AREA) - Muhammad Ridwan Adhitya; Nurika Suci Wulan; Putri Nur Azizah; Aris Prio Agus Santoso (International Journal of Law and Legal Ethics, 2020)
Law No.23 of 2004 explains the Elimination of Domestic Violence where there are sanctions threats for people who commit violence in the household, but the facts on the ground of domestic violence are still found due to the lack of supervision by the city / district government of women victims of domestic violence. The problem in this study is how the legal protection of women victims of domestic violence is viewed from a human rights perspective and what are the factors that influence domestic violence control. The form of this research is descriptive analysis, with secondary data collection, to find out the legal protection of women victims of domestic violence from a human rights perspective. The data obtained were analyzed qualitatively. Based on the results of the study determined that women in the city of Surakarta received legal protection by the city government of Surakarta through organizing, community empowerment through PTPAS, procurement of operational support facilities, provision of education and public outreach as the seriousness of the city government of Surakarta in handling cases of domestic violence against women. But it is still constrained by several factors including: Lack of awareness for victims of violence to report to the authorities, economic rehabilitation that is not effective, law enforcement officials who are less capable of handling cases of female violence, people who tend to be indifferent to incidents of violence in their environment.